La carrière d’un problème public mondial - Christophe Bonneuil; Marianna Fenzi (Revue d'anthropologie des connaissances)
The “genetic resource” concept was at the center of the 1992 Convention on Biological Diversity. How was this concept historically constructed? Which types of knowledge, imaginaries and forms of government of life had been embedded in this concept? How was the erosion of “genetic resources” constituted as a public problem and how did its place evolved within the wider population of other global environmental problems? Since 1992, the problem of “genetic resources” has been reframed and relabelled as ‘crop genetic diversity”, with a focus on in situ diversity, valued for the “ecosystems services” this diversity may provide. How can one account for such a new discursive framing which now dominates in the international arenas? Combining a cultural history of science, sensitive to the coproduction of knowledge and imaginaries, and a social problems sociology, sensitive to the dynamics of environmental problems within a mozaic of public arenas, this article analyses the trajectory of crop genetic diversity as a global public problem, from the middle of the 20th century to the present time.